Learner's Autonomy in Learning English as a Foreign Language : A Case Study at a State University in Bandung - Sakina, Rahma (2016)
This paper presents the outcome of a case study research which is particularly aimed at investigating dimensions and degree of learner autonomy in EFL learning particularly in an English education program, situations under which learners learn autonomously, and how lecturers' perception of learner autonomy influences their efforts to encourage learner autonomy. To collect the data, a questionnaire adapted from Murase (2009) was distributed to fourty first-year undergraduate students of a university in Bandung and interview was addressed to nine undergraduate learners and four lecturers. The findings showed that all dimensions of learner autonomy are found and each dimension is reflected in various degrees. The degree of technical and political dimensions of learner autonomy is in respect not as satisfactory as expected. However, the degree of learner autonomy in the psychological and socio-cultural dimension is high enough. There are four major aspects related to situations under which learners learn autonomously, including the subject matter, the lecturer, the time, and the challenging task. The lecturers' perception about learner autonomy influences their efforts to encourage learner autonomy in their courses. They attempted to promote learner autonomy in terms of the technical, psychological, and social dimensions. It is recommended for further research to investigate learner autonomy in a more specific context of class, for example learner autonomy in a speaking class, in order to get more in-depth data. ; Artikel ini menampilkan hasil penelitian studi kasus yang bertujuan untuk menginvestigasi dimensi dan tingkat learner autonomy dalam kegiatan pembelajaran Bahasa Inggris sebagai bahasa asing khususnya pada program pendidikan Bahasa Inggris, situasi dimana mahasiswa belajar secara otonomi, dan bagaimana persepsi dosen tentang learner autonomy mempengaruhi upaya mereka untuk mendorong otonomi mahasiswa. Untuk mengumpulkan data, sebuah kuesioner yang diadaptasi dari Murase (2009) didistribusikan kepada empat puluh mahasiswa tingkat satu di sebuah universitas di Bandung dan wawancara ditujukan pada sembilan mahasiswa dan empat dosen. Penemuan menunjukkan bahwa semua dimensi learner autonomy ditemukan dan masing-masing dimensi memiliki tingkat yang berbeda-beda. Tingkat learner autonomy dalam dimensi teknis dan politis tidak sesuai harapan. Akan tetapi, tingakt learner autonomy pada dimensi psikologis dan sosial-budaya cukup tinggi. Ada empat aspek yang berkaitan dengan situati dimana mahasiswa belajar secara otonomy, yaitu berkaitan dengan mata kuliah, dosen, waktu, dan tugas yang menantang. Persepsi dosen tentang learner autonomy mempengaruhi upaya mereka untuk mendorong learner autonomy di kelas mereka. Mereka berusaha mendorong learner autonomy pada dimensi teknis, psikologis, dan sosial. Disarankan untuk penelitian selanjutnya untuk menginvestigasi learner autonomy dalam konteks kelas yang lebih spesifik, contohya learner autonomy pada kelas speaking, untuk mendapatkan data yang lebih mendalam.